2013
DOI: 10.1136/bcr-2013-009677
|View full text |Cite
|
Sign up to set email alerts
|

Role of fine needle aspiration cytology in diagnosing filarial arm cysts

Abstract: SUMMARYFilariasis is prevalent in tropical and subtropical areas and is endemic in regions of India. Lymphatic filariasis in India is caused mainly by two species of nematodes: Wuchereria bancrofti and Brugia malayi, which invade the human lymphatic system. We report two cases of superficial cystic lesions of the upper limb revealed on fine needle aspiration (FNA) to be clinically unsuspected filariasis. Despite similar aetiologies, both cases revealed variations in aspirate nature, smear morphology and periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Epithelioid granuloma, giant cells and mixed inflammatory cells may be the result of host tissue response. 6 In our study maximum numbers of cases were reported as soft tissue swelling such as arm swelling (three cases) and one case at sub auricular site. Tandon et al, Srikanth et al and Panicker et al have reported microfilaria in fine needle aspiration cytology of arm cyst, forearm swelling.…”
Section: Discussionmentioning
confidence: 52%
“…Epithelioid granuloma, giant cells and mixed inflammatory cells may be the result of host tissue response. 6 In our study maximum numbers of cases were reported as soft tissue swelling such as arm swelling (three cases) and one case at sub auricular site. Tandon et al, Srikanth et al and Panicker et al have reported microfilaria in fine needle aspiration cytology of arm cyst, forearm swelling.…”
Section: Discussionmentioning
confidence: 52%
“…Culex mosquito transmits the bancroftian filariasis whereas Mansonia species transmits the brugian infections. 1,8 There are two different types of microfilaria found in humans: sheathed and unsheathed. Microfilariae bancrofti and Microfilariae malayi are sheathed whereas Microfilariae perstans and Microfilariae ozzardi are unsheathed varieties.…”
Section: Discussionmentioning
confidence: 99%
“…The parasites circulate in lymphatic and vascular compartments but the presence of filarial organism in tissue fluids and exfoliated surface material probably occurs owing to conditions causing lymphovascular obstruction resulting in extravasations of blood and release of microfilariae. 1,12 Rupture of vessels may have led to release of microfilariae into the subcutaneous tissue. Surrounding host tissue reaction probably led to the development of a well-defined cystic swelling containing multiple microfilariae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations